2015
DOI: 10.5120/21393-4436
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Application of Data Mining and Analytics in Education Domain

Abstract: Data Mining techniques and algorithms have been used on a large scale in almost all the sectors which range from computer science, manufacturing industry, and healthcare industry. A recently introduced concept of academic analytics uses the data mining algorithms on the educational data of students and gives certain insights about the expected performances of the students, expected retention rate of students and percentage of resources properly utilized. These results also help administrators in decision makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Based on analysis of students' study results, demographics and social data, at-risk students were identified for providing individual counselling Karkhanis and Dumbre (2015) Bridgewater College Tutors were provided with detailed information to discuss with students on their progress against targets and suggested actions Sclater et al (2016) Open Universities Australia…”
Section: Albany Technical Collegementioning
confidence: 99%
“…Based on analysis of students' study results, demographics and social data, at-risk students were identified for providing individual counselling Karkhanis and Dumbre (2015) Bridgewater College Tutors were provided with detailed information to discuss with students on their progress against targets and suggested actions Sclater et al (2016) Open Universities Australia…”
Section: Albany Technical Collegementioning
confidence: 99%
“…The program is authorized for use in predicting the future academic performance of students in an institution, in which it is destined to be used [31]. The staff is trained to apply the program during the entry of students' previous performances.…”
Section: Final Implementationmentioning
confidence: 99%
“…Association used two or more items that usually have the same type dataset used to identify the patterns. Apriori which is association algorithm is used to find relations between two or more entities in certain data environment such as mathematics and database [72,73]. Association using the support and confidence parameter to allow the association rule can be recognized.…”
Section: Unsupervised Data Miningmentioning
confidence: 99%